Keberlakuan Peraturan Dalam Undang-Undang Yang Tidak Kunjung Diterbitkan Peraturan Pemerintah Sebagai Peraturan Pelaksanaannya - Muhammad Yusuf (UIN Sunan Kalijaga Yogyakarta, 2022)
The conception of the rule of law, in the life of the state must be in accordance with the law. law is important. Regarding the Law on delegating detailed rules to the PP, it indicates that the Law and the Government Regulations become a single entity that makes the law clear, so that when a Law is not visited, it raises questions about the applicability of the Act. The formulation of the problem arises; How to apply the law that has not been issued by PP? What emerges from the Law for which the PP has not yet been issued? The method used is normative juridical, literature review is the focus of data collection and collection. This study concludes that a law whose PP has not been issued does not hold back the validity of the delegated law because the benchmark is that it is signed by the president or not signed for 30 days if it has been promulgated in the state gazette. The implication of enactment of a law that does not yet have a PP can affect the legal politics of the law that is not in accordance with what is desired and hampers its effectiveness. In addition, it is possible for violations to occur in the application of the law due to unclear regulations.